2016
DOI: 10.1128/jb.00239-16
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analysis of the Dps Response to Oxidative Stress

Abstract: Microorganisms have developed an elaborate spectrum of mechanisms to respond and adapt to environmental stress conditions. Among these is the expression of dps, coding for the DNA-binding protein from starved cells. Dps becomes the dominant nucleoid-organizing protein in stationary-phase Escherichia coli cells and is required for robust survival under stress conditions, including carbon or nitrogen starvation, oxidative stress, metal exposure, and irradiation. To study the complex regulation of Dps in E. coli,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 53 publications
0
18
0
Order By: Relevance
“…The quaternary structure of these protein families shows a high degree of variation: from monomeric rubrerythrin proteins (2,3); dimeric ironmineralizing encapsulin-associated firmicute (IMEF) proteins (4); dodecameric DNA Protection in Starved (DPS) cells proteins and DPS-like (DPSL) proteins (5)(6)(7)(8)(9); the 24-meric classical ferritins (Ftn) and bacterioferritins (Bfr) (10)(11)(12)(13); and the decameric encapsulated ferritins (EncFtn) (14,15). The rubrerythrin and DPS proteins play key roles in the protection of cells from oxidative stress, while DPS and the other members of the ferritin superfamily are vital iron stores (7,(16)(17)(18)(19)(20)(21)(22). These latter proteins oxidize and convert free Fe(II) to inert Fe(III) oxyhydroxide or Fe(III) phosphate mineral forms that provide a reservoir of bioavailable iron (23).…”
Section: Introductionmentioning
confidence: 99%
“…The quaternary structure of these protein families shows a high degree of variation: from monomeric rubrerythrin proteins (2,3); dimeric ironmineralizing encapsulin-associated firmicute (IMEF) proteins (4); dodecameric DNA Protection in Starved (DPS) cells proteins and DPS-like (DPSL) proteins (5)(6)(7)(8)(9); the 24-meric classical ferritins (Ftn) and bacterioferritins (Bfr) (10)(11)(12)(13); and the decameric encapsulated ferritins (EncFtn) (14,15). The rubrerythrin and DPS proteins play key roles in the protection of cells from oxidative stress, while DPS and the other members of the ferritin superfamily are vital iron stores (7,(16)(17)(18)(19)(20)(21)(22). These latter proteins oxidize and convert free Fe(II) to inert Fe(III) oxyhydroxide or Fe(III) phosphate mineral forms that provide a reservoir of bioavailable iron (23).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies of stochastic gene expression are supportive of the intriguing possibility of metabolic heterogeneity. For example, studies found that genetically identical cells in the same environment may produce different amounts of metabolically relevant proteins [28][29][30][31]. Recent computational work suggested that such different protein expression could give rise to metabolic heterogeneity in E. coli cells [32].…”
Section: Introductionmentioning
confidence: 99%
“…Strain 2P01AA had putative genes coding for heme oxygenase (HemO) and four genes coding for quorum-sensing molecules, which initiate biofilm biosynthesis and adhesion ( 12 ). Strain 50v1 had genes associated with betaine and choline uptake, which further allow for increased water retention in the cells ( 13 ), as well as alkyl hydroperoxide reductase subunit C and a DNA-binding protein (Dps), which has been shown to protect organisms from oxidative stress ( 14 ).…”
Section: Genome Announcementmentioning
confidence: 99%